Entomopathogenic fungi – Potential candidates for biocontrol of Helopeltis antonii Signoret in cashew - Nithin, A. Sobhana, M.S. Smitha, K.N. (Journal of Plantation Crops, 2019)
Evaluation of fungal entomopathogens, viz., Beauveria bassiana, Metarhizium anisopliae and Lecanicillium lecanii against tea mosquito bug (Helopeltis antonii Signoret), an insect pest of cashew revealed that these fungi are pathogenic to H. antonii. Mortality of H. antonii commenced after three days of inoculation, increased gradually with time and became evident at fifth day with 82.5 per cent, 85 per cent and 65 per cent respectively with B. bassiana, M. anisopliae and L. lecanii @109 spores mL-1. B. bassiana and M. anisopliae shown complete mortality at sixth day, whereas mortality rate with L. lecanii was 85 per cent. A field experiment was conducted in randomized block design for two consecutive years with these three entomopathogenic fungi @108 spores mL-1. Two rounds of spray were given by targeting flowering and nut set stage in the first year, instead of the routine three spray schedule on flushing, flowering and nut set; while routine three sprays were given in the second year. In the first year of field evaluation, least damage was observed in Kerala Agricultural University package of practices (KAU POP) with quinalphos, targeting both flowering and nut set stage. However, both B. bassiana and L. lecanii also recorded less tea mosquito bug damage and were comparable with KAU POP. In the second year, B. bassiana was on par with KAU POP and L. lecanii was superior to control. Highest nut yield was recorded in trees treated with B. bassiana followed by KAU POP.